Derivation by infrared spectroscopy with multivariate analysis of bimodal contaminant-induced dose-response effects in MCF-7 cells - Llabjani, Valon; Trevisan, Jülio; Jones, Kevin C; Shore, Richard F; Martin, Francis L (Environmental science & technology, 2011)
Toxic responses to contaminants following exposure concentrations typically used in laboratory tests may not reflect how biological systems respond to lower environmental levels from which hormetic effect mechanisms have been suggested. We investigated the pattern of dose-response in mammalian cells to various environmental contaminants using a range of concentrations that span those that are environmentally relevant (10(-12)M to 10(-3)M). MCF-7 cell cultures were treated for 24 h with benzo[a]pyrene (B[a]P), lindane (γ-hexachlorocyclohexane), or polybrominated diphenyl ethers (PBDEs) congeners (47, 153, 183, and 209), then fixed in ethanol and interrogated using attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy. Mode of action was further studied by examining if test agents stimulated cell growth or altered CYP1A1 expression. Bimodal dose response curves were observed when MCF-7 cells were treated with PBDEs or lindane. The first peak distribution was associated with lower doses (10(-12)M to 10(-9)M), while the second occurred only after MCF-7 cells were exposed to concentrations >10(-9)M. Cellular alterations associated with low-dose PBDEs were mainly due to lipid and secondary protein structural changes, whereas lindane induced DNA/RNA effects as well. In contrast, DNA-reactive B[a]P gave rise to a monotonic linear dose-response relationship and induced mainly DNA/RNA cellular changes. This study shows that environmentally realistic exposures to chemical contaminants can induce nonmonotonic dose-responses in cellular systems.